ANALYSIS OF THE TRENDS OF FISCAL POLICY AND ITS MONETARY EFFECTS IN THE IRAQI ECONOMY FOR THE PERIOD 2003-2020 - Dr. Yousef Ali Abd Al-Asadi; Zahraa Hayder Abd Al-Jabar Al-Battat (Scholar Express Journals, 2022)
The government can influence economic activity by using fiscal policy tools by making changes in taxes on the one hand or in the levels of public spending on the other, and the deficit occurs in most public budgets due to the lack of public revenues to meet the volume of public expenditures, and there are several mechanisms for financing the deficit, including bonds The treasury and the new cash issue, and that these mechanisms have severe effects on some monetary variables
Keywords: economy; including; financing; cash